2010
DOI: 10.1002/jbm.b.31641
|View full text |Cite
|
Sign up to set email alerts
|

Ag/SiOxCy plasma polymer coating for antimicrobial protection of fracture fixation devices

Abstract: Implant-related infections are often devastating situations in orthopaedic trauma surgery particularly if multiresistant bacteria are involved. Protection of the implant surface by an antimicrobial coating exhibiting activity against multiresistant bacterial strains is of high interest. Aim of this study was to investigate the antimicrobial effects of an Ag/SiO(x)C(y) plasma polymer coating for fracture fixation devices, such as nails, plates, and external fixators, including tests against methicillin-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 42 publications
5
54
0
1
Order By: Relevance
“…Moreover, confining the silver nanoparticles to a thin layer buried inside the polymer matrix avoids their direct exposure to the physiological tissues, thus reducing the potential toxicity of the layer toward eukaryotic cells. 22 Importantly, the antibacterial activity, arising from the dissolution of Ag + ions, 13 is not impaired given the water permeability of the PP-HMDSO film. 21 Saulou et al showed the release of Ag + ions into deionized water from silver nanoparticles, which had been embedded in a plasma polymer matrix deposited from HMDSO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, confining the silver nanoparticles to a thin layer buried inside the polymer matrix avoids their direct exposure to the physiological tissues, thus reducing the potential toxicity of the layer toward eukaryotic cells. 22 Importantly, the antibacterial activity, arising from the dissolution of Ag + ions, 13 is not impaired given the water permeability of the PP-HMDSO film. 21 Saulou et al showed the release of Ag + ions into deionized water from silver nanoparticles, which had been embedded in a plasma polymer matrix deposited from HMDSO.…”
Section: Discussionmentioning
confidence: 99%
“…13 In our PP100+Ag system, although the nanoparticles are not directly exposed to the outer coating's surface, dissolution and diffusion of silver ions out of the highly porous and water-permeable PP-HMDSO layer is readily possible. 21 Indeed, E. coli bacteria are not found to grow on the silver-containing layer.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Another investigation of the incorporation of silver into a silicone polymer coating for prostheses demonstrated significant activity in vitro and ex vivo against S. aureus and methicillin-resistant S. aureus [143]. Here, the silver-coated prostheses were explanted at various times and incubated with bacteria to test adherence.…”
Section: Orthopedic Hardwarementioning
confidence: 99%